The Battle of Two Bibles: When and How Did the King James Bible Gain Its Popularity over the Geneva Bible? - Chao, Hsing-Hao (Renaissance and Reformation / Renaissance et Réforme, 2023)
This article addresses two questions: “When did the King James Bible gain a foothold of popularity among the English people?” and “How did the Geneva Bible lose its popularity to the King James Bible?” By reviewing the post-1611 printing of these two versions of the Bible and examining the texts of the Paul’s Cross sermons and the parliamentary sermons between 1612 and 1643, I find that the King James Bible was already more popular than the Geneva Bible by 1620, and that the rising trend of the popularity of the King James Bible had become irreversible by 1630. By 1640, the battle of the two Bibles was long over. I also refute the assumption that the political authorities’ suppression of the Geneva Bible caused its defeat. Rather, I argue that the decrease in consumer demand for exegetical notes led to the demise of the Geneva Bible.